Answer:
(2xy +x+y)(3xy² -y)
= 6x²y³ -2xy²+ 3x²y² -xy +3xy³ -y²
(xy+3x+2)(xy-9)
= X²y² -7xy+3x²y -27x-18
(x²+3xy-2)(xy+3)
= X³y + 3x² + 3x²y² +7xy -6
Explanation:
For (xy+9y+2) and (xy-3)
(xy+9y+2) (xy-3)
= x²y² -3xy +9xy² -27y + 2xy -6
= x²y² -xy +9xy² -27y -6
For (2xy +x+y)(3xy² -y)
= 6x²y³ -2xy²+ 3x²y² -xy +3xy³ -y²
For (x-y)(x+3y)
= X² + 3xy -xy -3y²
= X² +2xy -3y²
For (xy+3x+2)(xy-9)
= X²y² -9xy +3x²y -27x+2xy -18
= X²y² -7xy+3x²y -27x-18
For (x²+3xy-2)(xy+3)
= X³y + 3x² + 3x²y² +9xy -2xy -6
= X³y + 3x² + 3x²y² +7xy -6